Riffaterre's Semiotic Study of the Qasidah Ya Badrotim in Maulid Ad-Diba'i Tradition - Nurul Khadroh Khadroh; Penny Respati Yurisa (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to explore the comprehensive meaning and symbolism of the qasidah "Ya Badrotim" in Maulid Ad-Diba' by Shaykh Abdurrahman Ad-Diba'i. It employs Michael Riffaterre's semiotic theory as an analytical framework, particularly focusing on the concepts of matrix, model, and variants to uncover deeper layers of meaning. This research is motivated by the limited scholarly attention given to specific qasidahs within Maulid Ad-Diba'i, and thus seeks to fill this gap. Using a descriptive qualitative method with a semiotic approach, the study reveals that the meaning embedded in the qasidah "Ya Badrotim" extends beyond literal description and reflects a complex semiotic structure. The analysis shows that the primary matrix represents the concept of the perfection of the Prophet Muhammad (peace be upon him), which is articulated through various symbolic models and variants, such as light, the full moon, and divine guidance. Additionally, the hypogram analysis demonstrates an intertextual relationship between this qasidah and earlier qasidahs within Maulid Ad-Diba'i. These findings confirm that Riffaterre's semiotic approach is effective in uncovering deeper meanings in qasidah texts. This study enriches Arabic literary semiotics and offers a deeper understanding of meaning in religious qasidah literature.